The "Exodus" in Jerusalem (Luke 9:31) : A Lukan Form of Israel's Restoration Hope - Shin, W. Gil, (Biblical Interpretation Series ;, 2022)
This study is a search for the specific form of Israel's restoration hope that underlies Luke's unique portrait of the transfiguration account and his framing of Heilsgeschichte, which reveals via a method of internarrativity a model of new exodus based on the Song of the Sea (Exod 15).